The mediating role of religious orientation on the relationship between luxury values, ethical values and buying behavior - Abdelkarim, Mohamed Abdallatif Abu Auf (2017)
Consumer behavior issues have become more heterogeneous because of cultural differences. This phenomenon makes it progressively important to understand factors impacting it. As such, this study examined the determinants of consumer buying behavior among Saudis and expatriates living in Riyadh, the capital city of the Kingdom of Saudi Arabia. Initially, this study discovered the role of religious orientation as a mediator between the relationships of luxury values, ethical value, media, word of mouth, price, motivation, and perceived cultural importance taken with consumer buying behavior. Partial Least Squares Method algorithm and bootstrap techniques were used to test the study hypotheses. The results provided support for most of the hypothesized relationships of the study. Specifically, ethical value, luxury values, motivation, price, and religious orientation were found significantly/positively related to consumer buying behavior which benefits the consumers. Also, creating value for the community was significantly/positively related to forms of consumer buying behavior. Additionally, religious orientation mediated between the relationships of ethical values, and perceived cultural importance taken with consumer buying behavior which showed consumers’ strong inclinations towards their ethical values and cultural perceptions. However, while creating value for the word of mouth, and price, a lack of significant relationship with religious orientation was found. As a whole, the results of mediation and other variables indicated that most of them were significant. The outcomes of this research seek to support industry and business practitioners in understanding the behavior of Saudis and expatriate consumers, and in using the ﬁndings to formulate strategies that enhance their competitiveness in the market. Finally, this research attempts to enrich marketing literature by providing empirical evidence on Saudis’ consumption behavior from the perspective of the Muslim population